2016
DOI: 10.1142/s0218348x16300026
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Charge Transmission in Gapped Graphene

Abstract: A new self-similar multibarrier system is proposed and used to study transmission of Dirac electrons in graphene. Such system is based on the scaling of the length and energy of the barriers. The use of self-similar structures allows us to compare the transmission in graphene and gallium arsenide (GaAs). The transmission coefficient for charge carriers in graphene shows a surprising scaling behavior structure, which is not seen in GaAs. The scaling properties are established as a function of three parameters: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…In this appendix we derive Eqs. (13), (14), (15), and (16). We start by studying each case out of the four possible for Eq.…”
Section: Appendix Amentioning
confidence: 99%
“…In this appendix we derive Eqs. (13), (14), (15), and (16). We start by studying each case out of the four possible for Eq.…”
Section: Appendix Amentioning
confidence: 99%
“…As we already mentioned, in previous works we have shown that graphene under appropriate nanostructuring can present self-similar characteristics 19 21 . To be specific, the transmission probability or transmittance sustains self-similar patterns with well defined rules.…”
Section: Resultsmentioning
confidence: 60%
“…As far as we know, materials such as SiO 2 , SiC, hBN, etc. could be used for this purpose 2224 .
Figure 1Self-similar multi-barrier structure 21 . ( a ) Potential or conduction band-edge profile of a Cantor-like multibarrier system.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, self-similar graphene structures, in which only the length of the barriers is scaled according to the Cantor set rules, display self-similar characteristics in the transmission probability or transmittance. These self-similar structures can be generated by nanostructured substrates 16 18 and inhomogeneous magnetic fields 19 . As we have documented graphene is the only material that manifests a fractal complex behavior in the electron transport.…”
Section: Introductionmentioning
confidence: 99%